An analysis of the state of the Customer-Retailer relationship to digital technology in retail businesses (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The retail industry has been utterly transformed by the arrival of digital technology, which has profoundly altered the dynamic between retailers and their customers. Electronic commerce (e-commerce), mobile apps, data analytics, & artificial intelligence (AI) are just a few examples of the digital technologies that have altered the traditional relationship between stores and their consumers. The increasing importance of data-driven decision-making in retail strategy, the trend towards more personalised shopping experiences, and the change in consumer expectations towards frictionless, omnichannel interactions are all important points of discussion. Customer engagement or loyalty have been boosted by these technologies, according to the report, thanks to real-time communication, greater convenience, and personalised marketing. In order to be competitive in the ever-changing retail industry, the paper finishes by stressing the need of merchants constantly innovating & building deeper consumer interactions with the use of digital technology.